Local Wisdom of Smoked Fish Processing as Tourism Product in Situbondo Regency - Junianingsih, Ika; Hakim, Luchman; Harahab, Nuddin (Graduate School, Universitas Brawijaya, 2014)
Marine and fisheries resources in Situbondo Regency were potential to supports seafood processing, e.g. traditional smoked processing of mackerel tuna (Euthynnus affinis Cantor) based on local wisdom. This research was aimed to assess and analyzes: the processing of smoked mackerel tuna based on local wisdom, public perception towards the processing of smoked mackerel tuna, and the quality of smoked mackerel tuna. The research carried out on January to April 2014, in Jangkar Village, Situbondo regency. The study included depth interview from key persons with questionnaire and organoleptic test. The public perception on smoked mackerel tuna was taken by questionnaire from 85 respondents, whereas the quality of smoked mackerel tuna was analyzed with laboratory proximate test. Result of this research showed that smoked mackerel tuna processing used traditional smoking instrument and fuel material. The smoking stall used several banana midrib stem above the furnace that made of cement and bricks, while the fuel use coconut coir which created the typical flavors of the smoked mackerel tuna. The average organoleptic value of the smoked mackerel tuna appearance is 7.89 (intact, clean, brown, very shiny specific type), flavors of 8.24 (less fragrant, smoked enough, without additional disturbing odor), taste of 8.41 (delicious, savory), texture of 7.40 (solid, compact, fairly dry, tight inter-flesh tissue), and colour of 7.20 (attractive, specific, shiny brown colour type). Public perception showed that the community knowledge on smoked mackerel tuna processing is good, creates good flavors of smoked mackerel tuna and favored by the community, thus also encourage the community to support the conservation of this traditional smoked processing. Lab analysis showed that the proximate value of 0.99% carbohydrates, 29.59% protein, 1.14% fat, 2.89% mineral, 1.88% ash, and 63.4% water. Processing of smoked mackerel tuna as tourism product of Situbondo Regency is worth and it has been given benefits to the increasing of community welfare, thus it need to be preserved to become sustainable. Keywords: culinary product, public perceptions, smoked mackerel tuna, traditional seafood processing.